The Smart Jacket for Cyclist - Fadzil, Aisyah; Jalaludin, Nor Anija; Sadun, Amirul Syafiq (Progress in Engineering Application and Technology, 2022)
Cycling has become one of the most popular activity sports as it also promotes a healthy lifestyle through increased physical activity. In fact, cycling has seen to be a low-impact, healthy sport that may be enjoyed by people of all ages, from children to elders despite it cheap and eco-friendly. While this trend appears to have many advantages, the issue of visibility, conspicuity and detection always be the key concerns for the cyclist since cyclist frequently struggle to stay safe among other vehicles. Due to the cyclist have a limited number of safety options available, such as side mirror and flashing lights that can give them little awareness on the road. Nevertheless, with the growth of technology smart jacket was developed with all-in-one system which help the cyclist feel safe and enjoy while riding. This includes, the turn signal direction and blindspot detection system. This turn signal is resembled as an arrow shape at the back of jacket to indicate the turning direction and enhance the visibility of cyclist. Besides that, the ultrasonic sensors are used to detect nearby obstacles at the blindspot area and alert the cyclist via buzzer and LED. This system provides them with additional time to avoid and prevent dangerous collisions. To conclude, after extensive testing and troubleshooting, the developed smart jacket successfully functions as it is water-resistant, washable, and it keeps cyclists safe and comfortable when cycling.